2016
DOI: 10.3390/rs8060460
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of MODIS LAI/FPAR Product Collection 6. Part 2: Validation and Intercomparison

Abstract: Abstract:The aim of this paper is to assess the latest version of the MODIS LAI/FPAR product (MOD15A2H), namely Collection 6 (C6). We comprehensively evaluate this product through three approaches: validation with field measurements, intercomparison with other LAI/FPAR products and comparison with climate variables. Comparisons between ground measurements and C6, as well as C5 LAI/FPAR indicate: (1) MODIS LAI is closer to true LAI than effective LAI; (2) the C6 product is considerably better than C5 with RMSE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
190
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 249 publications
(201 citation statements)
references
References 37 publications
11
190
0
Order By: Relevance
“…For example, Xu et al [64] assessed MODIS FAPAR through comparisons to ground measurements available from 2012-2016, obtaining a reasonable agreement (R 2 = 0.83, RMSE = 0.10) but with an overall overestimation tendency (bias = 0.08, scatters distributed within 0-0.2 difference). Similar results (R 2 = 0.74, RMSE = 0.15) were reported by Yan et al [59] using globally distributed FAPAR measurements. The study evidenced a clear overestimation of FAPAR over sparsely-vegetated areas, as noted previously in other studies [60].…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…For example, Xu et al [64] assessed MODIS FAPAR through comparisons to ground measurements available from 2012-2016, obtaining a reasonable agreement (R 2 = 0.83, RMSE = 0.10) but with an overall overestimation tendency (bias = 0.08, scatters distributed within 0-0.2 difference). Similar results (R 2 = 0.74, RMSE = 0.15) were reported by Yan et al [59] using globally distributed FAPAR measurements. The study evidenced a clear overestimation of FAPAR over sparsely-vegetated areas, as noted previously in other studies [60].…”
Section: Discussionsupporting
confidence: 78%
“…Similar underestimation behaviour was found by other studies when comparing MODIS LAI products and LAI retrievals from RTM inversion [59,63]. Yan et al [59] found RMSE = 0.66 m 2 /m 2 and RMSE = 0.77 m 2 /m 2 when comparing MODIS C6 LAI estimates with ground LAI actual and LAI e f f measurements respectively, as well as larger uncertainties in high LAI values. Regarding FAPAR, an overall negative bias is found for all biomes.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Two LAI data sets were used to calculate the growing season average LAI, namely the Boston University reprocessed MODIS Collection 6 LAI (hereafter LAI modis ) and the latest GIMMS-3g LAI. LAI quantifies the total area of green elements of the canopy per unit horizontal ground area 38 . The applied data sets are thus proxies for the total green LAI of all canopy layers, and can be used as a proxy for the green vegetation cover.…”
Section: Methodsmentioning
confidence: 99%